Aristotle's dream: Evolutionary and neural aspects of aesthetic communication in the arts. Issue 2 (14th January 2021) - Sütterlin, Christa; Yu, Xinchi
Abstract: Art in general perception is something that transcends our notion of reality. In view of the earliest findings in Paleolithic sites, their abstract appearance and sometimes ceremonial context increased their status of a secret language. Even the first figurative cave paintings remained in a context of an encoded semantic whole. The highly symbolic value of art seemed invulnerable. It was just the claim for "mimesis" in Greek antiquity (Plato) that urged artists to "realistically" depict what can be seen—as to stay in track of eternal messages behind. This devaluated the artistic oeuvre to a purely imitating craft and had to overcome at once several inherent obstacles. First, that reality (the phenomenal world) is in general only a pale reflection of what lays behind (Platonic ideas) and second, that the human eye, unlike the human mind, cannot penetrate to more than ephemeral impressions. Moreover, it mixed up reality with what we are able to see (i.e. visual perception), thus supposing a pinpoint representation of the world by our senses. Aristotle was the first to qualify art as picturing more than we usually are meant to see, filling the gap between the sensual and the spiritual world. Aristotelian aesthetics includes concepts of reduction and selection of composition and emotion, thus a summarized view within any performance of poetics or painting. And it took centuries to close the gap between natural and aesthetic perception or art. Life sciences in the 20th century discovered the evolutionary basis of sensory perception as being highly biased and organized, concept as emotion‐driven and thus, mentally equipped as well. This sets a new approach in our understanding of perception, art, and aesthetics as an ongoing communication in process on common bases. Art may cooperate or disagree, but never can cut the nexus with its perceptual prejudices and substrate.